Determinants of Factors Associated with Community Latrine Ownership in The Working Area of Serang City Public Health Center - Ratu Fitrianingrat Istiqomah; Lukman Waris; Prihayati (Health and Technology Journal (HTechJ), 2024)
Open defecation behavior is a serious threat to public health and the environment, making it an important problem in Indonesia. This figure makes Indonesia one of the three countries with the highest level of open defecation behavior in the world, namely India 12.9%, Indonesia 4.5% and China 1.3%. In Banten Province, access to sanitation is 86.45% as of August 2023, where there are still 458,717 heads of families out of a total of 3,274,172 heads of families who have not been able to access proper sanitation. Serang City occupies the 4th lowest position in terms of its people's ability to access proper sanitation with a percentage of 92.54%. This research aims to determine the relationship between determinants that influence latrine ownership in the community in the Serang City Health Center Work Area in 2023. The research uses a cross-sectional research design. This research aims to study the dynamics of the correlation between the independent variables, namely public perception about open defecation, socio-economic status and availability of facilities with the dependent variable, namely latrine ownership. This research uses an approach, observation and data collection taken at the same time at a certain time. The research was carried out in December 2023-January 2024 in the working area of ​​the Serang City Health Center, namely Sukawana Village, Serang City, Banten Province.